Use of dietary garlic \((Allium sativum L.) \) and Vietnamese balm\( (Elsholtzia ciliata)\) extract for prevention of Bacillary Necrosis in Pangasius (BNP) in striped catfish (Pangasianodon hypophthalmus) - Phuc Khang, Luu Tang; Vinh, Truong; Le Tho, Luong Thi; Tong, Nguyen Xuan; Phuong Dung, Tran Thi (Academia Journal of Biology, 2022)
Garlic (Allium sativum) and Vietnamese balm (Elsholtzia ciliata) are well-known herbs that have been widely used in Vietnamese traditional medicines. However, studies on the effects of these plants in improving the immune system of fish have received less attention. This study aimed to investigate the effect of ethanolic leave extracts from garlic and Vietnamese balm leaves on the growth and immune response of striped catfish (Pangasianodon hypophthalmus) for the prevention of Bacillary Necrosis of Pangasius. Bacillary Necrosis of Pangasius (BNP) caused by Edwardsiella ictaluri is the most serious disease occurring in farmed striped catfish in Vietnam. The experiment was in a completely randomized design with five triplicated treatments including 0% (control); 2% and 4% of garlic and 2% and 4% of Vietnamese balm leaves extract. Fish were soaked with E. ictaluri. Samples were collected on the days 7th and 14th of the growth experiment and days 3rd, 5th and 7th of the challenge test. Fish mortalities and immune response among challenge tests were also recorded. The results suggest that plant extracts possibly modulate the striped catfish’s immune response in a time and dose dependent manner. Specifically, diets enriched with extracts of A. sativum at 4% have great potential than Vietnamese balm extraction for improving striped catfish health by enhancing the immune system. After challenging with E. ictaluri, the accumulative mortality of fish in garlic and Vietnamese balm leaves treatments was lower than that of the control. The mortality of fish fed with 4% garlic extract was the lowest. These results indicated that supplementation of 4% garlic extract significantly improved the resistance to the BNP infection in striped catfish and has the ability to add fish feed in reality.